High Cryptococcal Antigenuria Prevalence in a Population of PLHIV with Neurological Symptoms Hospitalized in the Infectious Diseases Wards of the Centre Hospitalier Universitaire de Libreville, Gabon - Roger Hadry Sibi Matotou; Denise Patricia Mawili-Mboumba; Charlène Manomba; Bridy Chesly Moutombi Ditombi; Coella Joyce Mihindou; Dimitri Ardin Moussavou Mabicka; Arsène Mounomby; Solange Nzenze Afene; Marielle Karine Bouyou Akotet (Tropical Medicine and Infectious Disease)
Introduction: Cryptococcal meningitis is a major cause of death in HIV/AIDS patients due to the existence of Cryptococcus neoformans in the central nervous system. Our objective was to evaluate the prevalence of Cryptococcus antigenuria in a population of HIV-infected patients in Libreville, Gabon. Patients and Methods: This study was conducted from April to October 2021 at the Infectious Diseases ward of the Centre Hospitalier Universitaire de Libreville. Hospitalized patients with HIV were included. The detection of cryptococcal antigen (CrAg) in urine was performed using the Pastorex Crypto Plus Kit. Results: Out of the 255 PLHIV, 142 benefited from the CrAg detection. The prevalence of urine CrAg was 24.6% (n = 35). The majority of CrAg+ patients (82.8%; n = 29) were under 55 years old. Almost three-quarters of them (n = 25; 71.4%) had CD4 counts < 200, and 80.0% (n = 28) were at WHO clinical stages III and IV. All patients with neck stiffness at admission had a CrAg positive test. Conclusion: This study showed a non-negligible prevalence of Cryptococcal urinary antigen in HIV-infected patients with neurological symptoms. These data underline the importance of CrAg screening in routine care for better management of PLHIV.